Ours to eat and own: assessing the feasibility of a cooperative meal-kit service to improve food access - Joelle N Robinson-Oghogho; Joel Gittelsohn; Janice Bowie; Lois Dankwa; Roland J Thorpe (Public Health Nutrition, 2024)
Abstract